Neglected mycobiome in HIV infection: Alterations, common fungal diseases and antifungal immunity - Li, Shuang; Yang, Xiaodong; Moog, Christiane; Wu, Hao; Su, Bin; Zhang, Tong (Frontiers in Immunology, 2022)
Human immunodeficiency virus (HIV) infection might have effects on both the human bacteriome and mycobiome. Although many studies have focused on alteration of the bacteriome in HIV infection, only a handful of studies have also characterized the composition of the mycobiome in HIV-infected individuals. Studies have shown that compromised immunity in HIV infection might contribute to the development of opportunistic fungal infections. Despite effective antiretroviral therapy (ART), opportunistic fungal infections continue to be a major cause of HIV-related mortality. Human immune responses are known to play a critical role in controlling fungal infections. However, the effect of HIV infection on innate and adaptive antifungal immunity remains unclear. Here, we review recent advances in understanding of the fungal microbiota composition and common fungal diseases in the setting of HIV. Moreover, we discuss innate and adaptive antifungal immunity in HIV infection.